The Implementation of STP (Segmentation, Targeting and Positioning) in Determining Tourism Marketing Strategies (Studies on Kuno Kini Nanti in Trowulan, Mojokerto, East Java) - Kusnaini, Naimatul; Abdillah, Yusri; Fahrudi, Agung Nugroho Luthfi Imam (Wacana Journal of Social and Humanity Studies, 2023)
This research was conducted at one of the cultural tourism sites in Watesumpak Village, Trowulan, Mojokerto, East Java, namely Kuno Kini Nanti. Kuno Kini Nanti provides several tour packages to explore the historical sites of Majapahit Heritage in Trowulan. The management and marketing of Kuno Kini Nanti tourism have yet to run optimally, so an understanding of market segments, determining market targets and positioning is needed. This research used a case study method with a qualitative research approach to explore the marketing strategy of Segmentation, Targeting, and Positioning (STP) in developing Kuno Kini Nanti cultural tourism. The techniques for collecting the data, the researcher used observation, interviews, and documentation. The results of this research show that the types of purposeful culture tourists and serendipitous culture tourists with academic backgrounds and the millennial generation with an age range of 20-40 tears are the targets of Kuno Kini Nanti tourists’ because they are considered suitable for the tour packages that provided by Kuno Kini Nanti. Through the concept of “back to the Majapahit era”, Kuno Kini Nanti offers tourism activities to enjoy the cultural assets in Trowulan by traveling around using a shuttle bus, VW car or Vespa. Keywords : STP, cultural tourism, Kuno Kini Nanti